Reaping the fruits of research on microorganisms: Prospects and challenges for R&D and industry in Sri Lanka - Ruwan Fernando (South Centre, 2022)
When the Intellectual Property Bill designed to secure compliance with the Agreement on Trade Related Aspects of Intellectual Property Rights ("TRIPS Agreement") was challenged in the Supreme Court of Sri Lanka, the Court determined that the patenting of naturally occurring microorganisms by right holders would result in the increase of the prices of diagnoses and cures. The Supreme Court found that in the absence in the Bill of mitigatory measures -as allowed by the TRIPS Agreement- and of a working definition of the term "microorganism", there was a violation of the right to equal protection under Article 12 (1) of the Constitution. In the circumstance, the patent protection for microorganisms was narrowed down to transgenic microorganisms. The policy makers do not appear to have disregarded the positive impact of the Supreme Court determination by making the necessary statutory provisions and policy changes to facilitate the patent applications on transgenic microorganisms, while ensuring that local researchers are not restrained from gaining access to naturally occurring microorganisms for research and development.
Keywords: 300; Budapest Treaty; Chakrabarty Test; Deposit Requirement; Disclosure; Health; Intellectual Property; Microorganisms; Patent; Patentability Criteria; Research and Development (R&D); Sri Lanka; TRIPS; TRIPS Agreement